Smoking on hospital grounds and the impact of outdoor smoke-free zones. Issue 3 (1996) - Nagle, A L; Schofield, M J; Redman, S
Abstract : OBJECTIVES: To describe the type and location of smokers on the grounds of smoke-free public hospitals and to observe the impact of introducing smoke-free signs in outdoor areas of the hospital grounds. DESIGN: Observation study of outdoor smoking behaviour before and after the introduction of outdoor smoke-free signs at one hospital (H1) and at the same two time periods at a nearby control hospital (H2), which already had some outdoor smoke-free signs at Time 1. SETTING: The John Hunter Hospital (H1) in Newcastle, Australia and a nearby control hospital, Maitland Hospital (H2) in 1991. SUBJECTS: All people in defined outdoor sites of the two hospitals on seven randomly selected days over two weeks before and after the policy change were coded as either "smoker" or "non-smoker" and as either "staff", "patient", or "visitor". The number of smokers observed in each site was measured as a proportion of all smokers observed on the grounds of that hospital. INTERVENTION: Introduction of outdoor smoke-free zones and signs at H1. RESULTS: Less than 10% of observed outdoor smokers in both hospitals were patients, 40% were visitors, and more than 50% were staff. Of outdoor smokers, 82% were observed less than 10 m from entrances to the hospital building at time 1. After the introduction of signs in H1, a 4-percentage point decrease (P < 0.05) occurred in the percentage of smokers observed in smoke-free zones at time 2 (from 32% to 28%), compared with a 2-percentage point decrease (P > 0.05 at time 2 in H2 (from 48% to 46%). DISCUSSION: This observation study of smoking behaviour in hospital grounds highlights the need to reduce smoking among staff and visitors near hospital entrances. Specific strategies are discussed, which are likely to enhance compliance and hence enable the effective introduction of smoke-free policies on hospital grounds.